PROFILE OF 3’FLANKING REGION OF LEPTIN GENE IN SUMBA ONGOLE (SO) CATTLE - Widya Pintaka Bayu Putra; Paskah Partogi Agung; Ari Sulistyo Wulandari (Buletin Peternakan, 2017)
Leptin is a protein involved in the regulation of feed intake, fat metabolism, whole body energy balance and hematopoiesis in cattle. The diversity of the Leptin (LEP) gene in Indonesian indigenous cattle can be used as molecular livestock selection to improve productivity. The objective of this study was to identify Single Nucleotide Polymorphisms (SNP) in the 3’flanking region of LEP gene from 31 heads of Sumba Ongole (Bos indicus) cattle. A total of 17 SNP’s in the 3’flanking region (3506 - 4019 bp) of the LEP gene were identified according to GenBank: U50365. Five SNP’s (g.C3558T; g.G3566T; g.A3567C; g.G3574A; g.C3575A) were found in all samples. The moderate Polymorphic Informative Content (PIC) values (0.25<PIC<0.50) were found on nine SNP’s g.3565insG g.C3576A (0.29); g.C3577T (0.28); g.A3578C/G (0.45); g.C3579T (0.27); g.C3580T/A (0.47); g.C3581T (0.37); g.A3582G (0.38) and g.A3873G (0.35). The low PIC values (PIC < 0.25) were found on three SNP’s g.G3573C (0.21); g.G3661A (0.22) dan g.T3868C (0.17). Hence, a insertion mutation was found in position g.3565insG with frequency of 0.66. The next study of polymorphism in 3’flanking region trough more sample addition and production record are important to find the Marker Assisted Selection (MAS) for production traits.